Performance and carcass yield of broilers supplemented with plant extract during the finisher phase - Carlos,TCF (2014)
In this study, 600 one-day-old male Cobb 500 broilers were distributed according a completely randomized experimental design into the different dietary treatments. Broilers were fed the following dietary treatments: positive control diet (PC), containing 54 ppm zinc bacitracin; negative control diet (NC), with no inclusion of performance enhancers and 3% reduction in metabolizable energy, crude protein, and amino acid levels; PC up to 33 days and then NC, with the dietary addition of 75, 150, or 225 ppm plant extracts, until day 42 days of age. Broiler performance and carcass yield were evaluated. Data were analyzed using the Statistical Analysis System package (SAS Institute Inc., 2008), and submitted to polynomial regression analysis using the GLM procedure at 5% significance level. There was no influence of treatments on feed intake or weight gain, but feed conversion ratio of the broiler fed the plant extract was significantly higher (p<0.05) compared with those fed the antibiotic. There was no significant effect (p>0.05) of the applied treatments on carcass yield. We concluded that the replacement of performance-enhancing additives by plant extracts, at the evaluated inclusion levels, does not promote positive performance results.